State of the Art Review on Hempcrete as a Sustainable Substitute for Traditional Construction Materials for Home Building - Wei Tong; Ali M. Memari (Buildings)
Currently, the construction industry relies mainly on non-environmentally sustainable materials such as fired clay brick, concrete, and steel, which significantly contribute to global carbon dioxide generation, leading to environmental degradation. In response to mounting environmental concerns, there is a growing emphasis on developing and utilizing low-impact materials that mitigate the ecological footprint of construction activities. This review offers a detailed overview of current formulations and applications of hempcrete and compares the performance of different types of hempcrete as construction materials. Additionally, this paper seeks to evaluate the potential of hempcrete as a sustainable substitute for traditional construction materials with high energy demands and significant CO2 emissions based on life cycle assessment (LCA). Furthermore, this study summarizes current challenges and prospects for composite innovations in hempcrete, emphasizing the need for standardized product control and broader industrial acceptance, thus providing useful insights for practitioners and researchers in the field.